Underweight problems in Asian children and adolescents - Mak, Kwok-Kei. (2013)
Most reviews on weight status have focused on obesity, and little information on underweight children is available. This review aimed to examine the prevalence and trends of underweight status among Asian children and adolescent populations in the last two decades. A systematic review of publications between the years 1990 and 2010 was conducted. Underweight in children and adolescents was relatively more prevalent in the South and West Asian countries than in the East Asian countries. In general, underweight was more prevalent in boys within the South and West Asian countries, while it was more prevalent in girls within the East Asian countries. Increasing trends of prevalence of underweight were common among children and adolescents in South and West Asia. Specific public health policies should be formulated to combat the underweight problems in less-developed countries.